Speaking and Writing Errors Made by Students of English Education - Diemroh Ihsan (Universitas Negeri Malang, 2016)
This study was based on the "controlled" speeches and term papers of students of the English Education, Sriwijaya University. The subjects were 20 students of the fifth semester, who were taking speaking V in the year 1994/1995. They were taken from 80 students as the population. Two approaches were employed in the study: description and analysis. The study described the kinds of errors found both in spoken and written data. Then, it analyzed the sources of the errors. It was concluded that the subjects were good as their errors did not exceed 10% in terms of the total sentences they made in speaking as well as in writing. Speaking and writing errors were relatively the same in terms of the kinds of errors and their causes. In terms of speaking, the students could be in scale 3. In writing, the students could belong to level 3, that is, minimum professional proficiency.